Burned : A PRETTY LITLE LIARS NOVEL - Shepard, Sara, 1977-, (Harper Teen, 2013)
Deciding to come clean about a terrible mistake they committed during spring break, high school seniors Aria, Emily, Hanna, and Spencer hope to end the blackmail of a ruthless stalker who retaliates by plotting a murderous revenge